ChemInform Abstract: New MCR Based on Intramolecular Heck Reaction under Aerobic Conditions: A Direct Access to Cytotoxic Fused N‐Heterocycles. Issue 15 (April 2015) - Adepu, Raju; Prasad, Bagineni; Ashfaq, Mohd Ashraf; Ehtesham, Nasreen Z.; Pal, Manojit
Abstract: Title compounds are prepared from isatoic anhydride (I), aromatic 2‐bromo‐substituted arylaldehydes, and allyl amine.